Recent Development in the Structural Modifications of Monocarbonyl Analogues of Curcumin and their Improved Biological Activities: A Review - Negi, Nidhi; Chand, Garima; Kholia, Deepa; Anand, Rahul; Upadhyay, Santosh Kumar; Tewari, Geeta; Joshi, Penny (Pharmacognosy Reviews)
Curcumin is a polyphenolic constituent of the rhizome of Curcuma longa and is known for its versatile biological properties like antioxidant, anti-bacterial, anti-cancer, anti-inflammatory, antiviral and so forth. Despite possessing a wide range of reported pharmacological effects, its clinical applicability is restricted, because of the poor bioavailability and poor solubility due to the presence of β-diketone moiety in its structure. Several strategies have been developed in the past decade to overcome this disadvantage. One important approach is designing and synthesizing new curcumin derivatives which have improved therapeutic properties and bioavailability than curcumin. Therefore, Monocarbonyl Analogues of Curcumin (MACs) have been synthesized with improved physiological properties and pharmacological effects. There is also a continued interest in synthesizing analogues that should have almost identical safety profiles like curcumin, but increased activity with enhanced oral bioavailability. This review describes the recent development in the structure modification of MACs and focuses on their anti-oxidant, antibacterial, anticancer activities and other biological activities.
Keywords: Monocarbonyl analogues; Curcumin; Antioxidant; Antibacterial; Anticancer